How Do Language Professionals Organize Themselves? An Overview of Translation Networks - McDonough, Julie (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractThis paper provides a framework for categorizing and describing translation networks. It defines and outlines four main categories of translation networks: profession-oriented, practice-oriented, education-oriented and research-oriented. To better describe these networks, variables affecting their structure and composition are also explored. Finally, the TranslatorsCafé network is analyzed to demonstrate how this framework could be applied to future studies.